2018
DOI: 10.21608/ejcm.2018.11046
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension and Quality of Life among Hypertensive Patients in An Egyptian Village

Abstract: Background: Systemic Hypertension (SH) is a major cardiovascular risk factor with a high prevalence in almost all countries and is one of the leading risk factors for global mortality. It is estimated to have caused 7% of disease burden in 2010 and 9.4 million deaths. Studies have been conducted to illustrate the negative effect of systemic hypertension on health-related quality of life. Objective: To measure the prevalence of hypertension and its risk factors among residents of a village in Menoufia governora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…Concerning past medical history, about half of the study participants had diabetes at 10 years old, besides hypertension, neurological, and foot problems. This result is in line with Gabal et al (2018) , Jia and Sowers (2021) , and Kassem et al (2022) , who reported that patients with metabolic disorders, including insulin resistance and diabetes, have a high prevalence of hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…Concerning past medical history, about half of the study participants had diabetes at 10 years old, besides hypertension, neurological, and foot problems. This result is in line with Gabal et al (2018) , Jia and Sowers (2021) , and Kassem et al (2022) , who reported that patients with metabolic disorders, including insulin resistance and diabetes, have a high prevalence of hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…hypertension individuals, in agreement with our study Mohamed et al [23] studied 600 individuals in rural areas in Egypt and found that the mean HRQOL scores among the hypertension community were highly significantly lower than the nonhypertensive group (P<0.0005). Also, this finding agrees a study in 2002 by Al-Ghamdi et al [24] at primary health care facilities in Al-Khobar, Saudi Arabia, for comparison the HRQOL of hypertensive patients with a control group, 404 subjects were interviewed (202 cases and 202 controls).…”
Section: Experimental Controlssupporting
confidence: 93%